DNA DIAGNOSTICS AND MUTATION SPECTRUM OF THE GENE FBN1 IN MARFAN’S SYNDROME - Yu. A. Rogozhina; V. A. Rumyantseva; A. A. Bukaeva; E. V. Zaklyazminskaya (Российский кардиологический журнал)
Aim. The development of an optimal protocol for diagnostic search for mutations with the use of the new generation sequencing technique (NGS) and evaluation of the mutation spectrum in Russian selection of the patients with Marfan syndrome.Material and methods. Totally 32 patients included with Marfan syndrome. For 24 the direct sequencing was done by Sanger, of 24-32 exons FBN1. For 10 persons the analysis performed of coding exons and close introns regiones of the gene FBN1 with the preparation of fragmented libraries and performing of NGS on the IonTorrent platform. For 12 persons the mutations search was done with the use of automatically developed panel of Ampliseq primers for multiplex amplification of coding regions of genes that are responsible for the connective tissue development.Results. In investigation of 24-32 exones of FBN1 we found 3 replacements (p.C921R, p.C950S and p.I1048T). In complete analysis of FBN1 gene by fragmentation check of replacements we found 4 premature stop-codons (p.Y181*, p.R516*, p.Q1811*, p.R2776*) and 3 missense variants (C739W, p.C1095S, p. C2468R). In addition, there was deletion with the shift of translation frame and occurence of stop-codon in the 9th exon (c.661delT). In one female patient there was replacement variant c.4942+4A>G, with non-defined clinical significance. With the complete analysis of FBN1 using Ampliseq there were 2 premature codons found (р. Q520*, p.K2838*) and 2 deletions with the translation frame shift (c.40_49del, c.6751del). In 6 from 12 there were missense replacements found (p.N2144S, p.A986T, p.C2390S, p.С2276W, p.C1777R and p.C2363G).Conclusion. In the case of absense of the “hot spot” exons, invention of NGS allows for optimization the search of mutations even in such long genes as the FBN1. Medical-genetic consultation and DNA-diagnostics are the integral methods for multidisciplinary care.